PENGAMATAN PERTUMBUHAN KAMBING PERANAKAN ETAWAH YANG DIPELIHARA INTENSIF DI KABUPATEN MANOKWARI - Nani Zurahmah (Fakultas Peternakan Universitas Papua, 2018)
This study aims to observe the growth of Peranakan Etawah goats (PE goat) that are maintained intensive in Manokwari regency. The research material used was 50 PE goats that were born from 42 parents. The research method used is suvei with case study technique. The sample of pregnant goat used was taken by purposive sampling. The observed variables were birth weight, body weight 90 days and daily weight gain of goats studied. Data on the results of the study were analyzed using the t-test to compare growth of the goats observed by type of birth (single vs twin) and sex (male vs female). The results of statistical analysis showed that birth weight (3.01 ± 0.44 kg) and body weight 90 days (9.09 ± 1.77 kg) in single-birth-type PE goats were higher (P <0.05) than birth weight ( 2.76 ± 0.44kg) and body weight of 90 days (8.07 ± 1.67kg) in twin goat birth type. However, the single birth weight of single-birthed PE goats (65.58 ± 17.53g) was statistically not different (P> 0.05) with the multiple births (58.96 ± 19.23g). Also known that birth weight (3.16 ± 0.47 kg) and body weight 90 days (9.22 ± 1.77 kg) in male PE goats was higher (P <0.05) than birth weight (2.68 ± 0.29kg) and body weight 90 days (8.27 ± 1.71kg) in the female. While the weight of male goat PE (64.26 ± 18.86g) was statistically not different (P> 0.05) with the female (62.18 ± 17.79g).